TRANSITIONING PESHAWAR BRT FROM DIESEL-HYBRID ENGINES TO HYDROGEN FUEL CELLS: SOCIO-ECONOMIC IMPACT & FEASIBILITY - Muhammad Bilal; Emran Ullah Khan; Ateeb Ali Khan (Spectrum of Engineering Sciences, 2025)
Peshawar's Bus Rapid Transit (BRT) system holds great relevance in driving Peshawar transport, such a revolutionary system which has created thousands of jobs, and created more business opportunities than ever. But it needs to be improved with the hydrogen fuel cell technology (HFC), transition of Peshawar's Bus Rapid Transit (BRT) system from a conventional fuel transport to a futuristic one like that of Hydrogen fuel cell (HFC) will increase chance to adapt to a sustainable urban transport, reduce greenhouse gas emissions, and improve socio-economic elements in the region. As per the census carried out the Hydrogen Fuel Cell Electric Buses (HFCEBs) market value is estimated to be around 8.31 Billion, with an annual growth of 19.78% indicating its total market value to 20.49 Dollar by 2030. Transition of the Peshawar BRT systems to all Hydrogen Fuel Cell Electric Buses (FCEBs) will offer operational advantages to the transport infrastructure of the city, increasing the buses extended ranges to far side of the city, enhancing rapid refueling systems, all of which aligns with the demands for a high-frequency and swift BRT system. Implementation of Hydrogen Fuel Cell technology will enable BRT Systems to produce zero carbon emissions, help in decreasing air and water pollution, along with lowering the cost of operation for driving the BRT System.